Enhanced load frequency control response with integration of supervisory controlled superconducting magnetic energy storage system in wind-penetrated two-area power system. Issue 5 (October 2017) - Dar, S Zahid Nabi; Mufti, MD
This work concentrates on the integration of superconducting magnetic energy storage system with wind-penetrated two-area power systems. Each area is incorporated with a superconducting magnetic energy storage unit. The superconducting magnetic energy storage unit is controlled using an adaptive predictive control strategy, which takes care of constraints on converter power rating of superconducting magnetic energy storage unit. The proposed scheme is tested by carrying out simulation experiments in MATLAB and Simulink environment. The simulation results demonstrate the improvement in frequency and tie-power oscillations. In addition, the control objectives related to superconducting magnetic energy storage unit are also depicted.